Mind the gap: global quality norms, national policy interpretations and local praxis in Timor-Leste. Issue 3 (3rd May 2016) - Shah, Ritesh; Quinn, Marie
Abstract : Increasingly, the imperative for improving educational quality in schooling systems throughout the developing world is harnessed to a particular set of teaching and learning practices, such as child-centred, child-friendly or learner-centred pedagogy (LCP). Such was the case in Timor-Leste where, after independence, LCP was heavily promoted as a panacea for an education system that was perceived to be irrelevant, outmoded and of poor quality. While LCP was readily adopted into policy discourse, less support and attention were given to the substantive incorporation of LCP into teacher practice. When strategically borrowed in such a fashion, the paper suggests little promise remains for LCP to meaningfully improve student learning processes or outcomes in Timorese classrooms.